Attitudes of young consumers towards innovations on the food market = Postawy młodych konsumentów wobec innowacji na rynku żywności - Barska, Anetta (Zielona Góra: Faculty of Economics and Management Press)
In this article, the author presents the results of her own surveys concerning attitudes of young consumers ? living in the border areas of Poland, Czech Republic, Slovakia and Germany - towards innovation on the market of food products. Innovative food is positively accepted by the young consumers, although it should be noted that large group of consumers are driven by the habits, especially Polish and Czech consumers. The process of diffusion of innovations on the food market among young consumers depends on the country they live in, gender (women considerably faster accept innovations) but is not determined by high incomes.
Keywords: innowacje; młody konsument; zachowania konsumentów; dyfuzja innowacji; innovation; young consumer; consumer behaviour; diffusion of innovations